A Castle in the Sky? The Icelandic Ban on Non-Therapeutic, Non-Consensual Interventions on Intersex Children in Context - Alaattinoğlu, Daniela; Ragnarsson, Kári Hólmar (Sweet & Maxwell, 2026)
Framing non-consensual, medically unnecessary interventions as human rights violations has become a priority for global intersex movements in recent years. However, establishing binding legal norms in this area remains challenging. Few countries have prohibited such interventions and scholarly discussions on these bans are still in their early stages. This article offers a contextual case study of Iceland’s 2020 ban, as one of the few countries to outlaw non-consensual, non-therapeutic interventions on children with variations in sex characteristics. Drawing parallels with similar bans in other European countries, the article argues that framing the issue in terms of rights has been effective in mobilising action, building consensus and driving legislation.Yet, the broad and ambiguous framework underlying these laws appears to result in ineffective implementation, making such legislative bans at risk of becoming symbolic achievements for states, offering limited protection and few remedies for intersex people.